A novel spheroid-based co-culture model mimics loss of keratinocyte differentiation, melanoma cell invasion, and drug-induced selection of ABCB5-expressing cells - Klicks, Julia (BMC Cancer, 2019)
BACKGROUND: Different 3D-cell culture approaches with varying degrees of complexity have been developed to serve as melanoma models for drug testing or mechanistic studies. While these 3D-culture initiatives are already often superior to classical 2D approaches, they are either composed of only melanoma cells or they are so complex that the behavior of individual cell types is hard to understand, and often they are difficult to establish and expensive. METHODS: This study used low-attachment based generation of spheroids composed of up to three cell types. Characterization of cells and spheroids involved cryosectioning, immunofluorescence, FACS, and quantitative analyses. Statistical evaluation used one-way ANOVA with post-hoc Tukey test or Student’s t-test. RESULTS: The tri-culture model allowed to track cellular behavior in a cell-type specific manner and recapitulated different characteristics of early melanoma stages. Cells arranged into a collagen-IV rich fibroblast core, a ring of keratinocytes, and groups of highly proliferating melanoma cells on the outside. Regularly, some melanoma cells were also found to invade the fibroblast core. In the absence of melanoma cells, the keratinocyte ring stratified into central basal-like and peripheral, more differentiated cells. Conversely, keratinocyte differentiation was clearly reduced upon addition of melanoma cells. Treatment with the cytostatic drug, docetaxel, restored keratinocyte differentiation and induced apoptosis of external melanoma cells. Remaining intact external melanoma cells showed a significantly increased amount of ABCB5-immunoreactivity. CONCLUSIONS: In the present work, a novel, simple spheroid-based melanoma tri-culture model composed of fibroblasts, keratinocytes, and melanoma cells was described. This model mimicked features observed in early melanoma stages, including loss of keratinocyte differentiation, melanoma cell invasion, and drug-induced increase of ABCB5 expression in external melanoma cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5606-4) contains supplementary material, which is available to authorized users.